Unlocking investment and innovation in dryland crops: A business forum on sorghum and groundnuts in Tanzania - Binagwa, Papias H.; Stiliwati, Fikiri A.; Mwenda, Emmanuel T.; Sikitu Kazungu; Mchau, Devotha; Mwamahonje, Andekelile; Gichuru, Lilian (TARI, 2025)
Dryland crops such as groundnuts, sorghum, mungbean, cowpea, millets, and pigeon pea play a vital role in food and nutrition security, climate resilience, and livelihoods in Tanzania’s semi-arid regions. Despite their importance and adaptability to local agro ecologies, these crops remain under-commercialized, under-invested, and marginalized in the national agrifood systems conversations. Many improved varieties of these crops have been developed and released by national and international research institutions, but variety adoption and quality seed use remain low. This is attributed to several causes including weak linkages between research outputs and arket demand. Moreover, private sector involvement for these value chains is limited, primarily due to perceptions of low commercial viability, unpredictable demand, and a lack of investment incentives. Furthermore, value-added traits of these improved varieties are not sufficiently communicated to market actors to drive commercializatin decisions. Across the seed supply chains, several challenges continue to persist, ranging from misaligned early generation seed (EGS) systems, low use of variety licensing mechanisms to the lack of platforms for dialogue between farmers, breeders, seed producers, and off-takers. These bottlenecks hinder market development and restrict opportunities for scaling, enterprise growth, and employment generation within dryland crop value chains. Through science-based, locally led partnerships, CIMMYT and partners such as TARI seek address some of these challenges to accelerate the adoption of improved dryland crop varieties. With this hindsight, this Business-to-Business (B2B) forum was organized to offer a platform for learning, networking, and joint problem-solving, aiming to catalyse business growth and competitiveness within the sorghum and groundnut value chains. The event provided participants with access to knowledge on new varieties from researchers, connected potential business parters and mentors, and providing a space to co-develop practical solutions to long-standing challenges affecting the dryland crop sector.